Design of a Village Newspaper Application (Kordes) in Realizing a Digital Village in the Village of Dusun Baru V koto, Mukomuko Regency, Based on Android - Hendrawan, Jodi; Devi Perwitasari, Ika; Felawati, Fatima (Sustainability (STPP) Theory, Practice and Policy, 2022)
KorDes is a village newspaper application that contains the latest information that occurs in the village, information on village developments and information on village data as a form of realizing a digital village. This KorDes application was formed as a solution for the people of Dusun Baru V Koto Village, Mukomuko Regency who have difficulty in accessing valid and growing information in the village. In designing the KorDes application, it will be implemented based on Android. Android-based will make it easier for people to access via their smartphones which can be accessed at any time. The design of the application uses the technique of developing UML (unified modeling language) diagrams which makes it easier to document and define applications.